2004
DOI: 10.1021/jm0494568
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Trace Metal Concentrations in Malign and Benign Human Prostate

Abstract: Imbalance in the composition of trace metals, recognized to be essential to normal human homeostasis, besides the accumulation of potentially toxic or nonessential trace metals, may cause disease. Thus, there is a need for their analysis in cancerous and noncancerous human tissues to examine the relationship between cancer and these elements. Trace metal concentrations including Cd, Ni, Zn, Cu, Fe, Mg, and Ca in both malign and benign prostate samples were determined by atomic absorption spectrophotometry. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
47
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 18 publications
4
47
2
1
Order By: Relevance
“…Obtained concentration ranges for various elements in our study were similar to that reported in literature for wet benign and malignant prostatic tissues [10,12,13]. Of the five measured elements, a significant difference was noticed in the concentration of Se and Zn only between PCa and BPH groups.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Obtained concentration ranges for various elements in our study were similar to that reported in literature for wet benign and malignant prostatic tissues [10,12,13]. Of the five measured elements, a significant difference was noticed in the concentration of Se and Zn only between PCa and BPH groups.…”
Section: Discussionsupporting
confidence: 88%
“…By contrast, isolated studies have reported a significantly higher tissue level of zinc in PCa as compared to BPH [12] and normal prostatic tissue [27] or an insignificantly lower level of zinc level in PCa as compared to normal prostatic tissue [28]. There are conflicting reports about tissue zinc levels in BPH as well; some found a decrease [17] while others an increase [13] or no change [18,26] as compared to normal prostatic tissue.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In that study, this finding was suggested to be related to suppression of oncogen-induced bowel carcinogenesis by Mg (Mori et al, 1992). In a previous study, it was found that Mg levels were higher in tissue specimens obtained from patients with prostate cancer than those obtained from benign prostate hyperplasia (Yaman et al, 2005). In our study, serum Mg levels were found to be significantly higher in the patients with prostate cancer compared to controls.…”
Section: Discussionsupporting
confidence: 65%
“…This can explain increased Cu levels in involved tissues (Uauy et al, 1998;Majumder et al, 2009). In a previous study, Cu levels found to be slightly higher in tissues with prostate cancer compared to those from benign prostate specimens (Yaman et al, 2005). In another study, copper levels at hair and nail were found to be significantly higher in patients with prostate cancer (Karimil et al, 2012).…”
Section: Discussionmentioning
confidence: 89%